FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR SECARA SUKARELA PADA PERUSAHAAN NON-KEUANGAN YANG TERDAFTAR PADA BURSA EFEK INDONESIA - Jessica Triharyanto; Magda Siahaan (E-Jurnal Akuntansi TSM, 2021)
This study aims to examine the effect of audit opinion, management turnover, size of public accountant, audit delay, client company size, institutional ownership, financial distress and return of assets to voluntary auditor switching in non-financial companies listed on the Indonesia Stock Exchange in 2016-2018. The approach used in this study is based on an empirical approach. The sampling method used was purposive sampling method with 253 companies. The analysis technique used in this study is logistic regression. Based on the results of the analysis shows that the size of public accountant has a negative effect on the chance of voluntary auditor switching, while audit opinion, management turnover, audit delay, client company size, institutional ownership, financial distress and return of assets have no effect on the chance of voluntary auditor switching.